Leading by example: A three-wave sequential mixed method food safety study - Lin, Naiqing; Paez, Paola (My University, 2020)
(Best Paper Award/ 253 submissions) According to the most recent government data, approximately 61% of foodborne illness outbreaks were attributed to lack of personal hygiene and improper food handling by employees in the foodservice industry. Foodservice employees fail to adhere to safe food preparation practices, may directly introduce pathogens that can cause illness and death. Few qualitative studies have examined the barriers of effective managerial practices that influence employee’s food safety behaviors. Therefore, the purpose of the study is to explore employees’ perspectives about managerial practices that influence their food safety behaviors.
Keywords: foodborne illness; food safety; foodservice; managerial practices